Hypoglycaemic, anti-hyperlipidemic, and anti-inflammatory activities of Asparagus africanus (Asparaceae) extract on high-fat diet/streptozotocin-induced diabetes in Wistar rats - Focham Evans Ngwenah; Oumar Mahamat; Tume Christopher (Asian Pacific Journal of Tropical Biomedicine)
Objective: To investigate the toxicity and effect of the extract on some complications of diabetes in Wistar rats. Methods: Type 2 diabetes was induced by a combination of a high-fat diet and streptozotocin (35 mg/kg, i.p.). Aqueous extract of Asparagus africanus (EAA) was prepared and administered (p.o.) for 28 d to groups of diabetic rats as well as to groups of normal rats for toxicity. Fasting blood glucose levels, inflammatory cytokines, and lipid profiles were assessed in diabetic rats. Body and organ weight as well as liver and kidney functions were examined to assess the sub-acute toxicity. Results: EAA for 28 d did not affect the body weight, the weight of the liver, kidney, and heart as well as the serum level of aspartate aminotransferase, alanine aminotransferase, urea, uric acid and creatinine in normal rats. In diabetic rats, the administration of EAA significantly lowered hyperglycemia, reduced interleukin (IL)-6, IL-1β, and tumour necrosis factor-α levels, and increased the level of IL-10. EAA also lowered cholesterol, triglyceride, and low-density lipoprotein cholesterol levels and augmented high-density lipoprotein cholesterol in the serum. As a result of the anti-lipidemic effect, EAA reduced the atherogenic index, Castelli indices, and atherogenic coefficient in diabetic rats. EAA showed the presence of flavonoids, alkaloids, tannins, saponins, terpenes, and steroids. Conclusions: The findings of this study demonstrated that EAA is safe. It has the potential to reduce the glucose level and the risk of inflammation and atherogenesis in diabetic patients.